Analisis Tingkat Kepuasan Siswa terhadap Media Pembelajaran PowerPoint Interaktif Berbasis RPE pada Materi Listrik Searah - Fitroh, Ummi Nuzulul; Ellianawati, Ellianawati; Susilo, Susilo (UPEJ Unnes Physics Education Journal, 2021)
This study aims to analyze the responses of class XII students at MA Nahdlatul Muslimin Kudus to the use of interactive PowerPoint learning media based on RPE (Realistic Physic Education) in the physics learning process. The research sample was 25 students. In this study, there were two problems that were investigated, namely related to student responses to the use of interactive media in the physics learning process and the level of student preference for the media that had been presented in the physics learning process in the classroom. The data obtained in this study were in the form of student response questionnaire data and physics teacher interviews. The data were analyzed using descriptive analytical methods to obtain answers to the problems in the study. The results of the average level of student satisfaction with the use of interactive powepoint media based on RPE (Realistic Physic Education) were 3.25 with the very good category. The result of the level of liking was obtained that 55% of students gave very interesting responses, as many as 32% of students gave interesting responses and as many as 13% of students gave casual responses to interactive media applied in the physics learning process. This shows that students like interactive learning media in the physics learning process, so that learning is more effective and less boring.